Non-trivial impurity and field effects in topological Kondo insulator SmB6. (2022) - Guha Roy, Sayak; Das, Anirban; Mukherjee, Shantanu
Abstract: Topological Kondo Insulator SmB6 is a strongly correlated material where a spin–orbit interaction between the localized odd-parity f-electron and even parity d-electron levels lead to a band inversion and opening of an insulating gap. The non-trivial topology (Z2 = -1) leads to the formation of a topologically protected conducting surface state due to the presence of strong correlation physics. Although the bulk material is known to form a topological Kondo gap, recent magnetic quantum oscillation experiments on SmB6 find an unconventional Fermi surface whose origin remains a matter of intense debate, and the possible role of topological surface state and impurity induced in-gap states have been proposed. By utilizing a realistic multi-orbital tight-binding Hamiltonian, this work aims to develop a microscopic model to study the effects of perturbations like external magnetic fields, and impurities on the low energy bulk and topological surface state properties of SmB6 . We further examine the role of an external electric field in tuning the non-trivial topological surface state in SmB6 and provide experimentally observable signatures in the local density of state (LDOS) near non-magnetic and magnetic impurities. Additionally, we study the surface Ferromagnetism that arises in SmB6 as observed by magnetoresistance experiments.